Combining Two Performance-based Assessment Methods of Logbook and DOPS in Field Internship of BSc Anesthesiology Students - Fakhrosadat Mirhosseini; Houman Manoochehri; Soolmaz Musavi; Fateme Hasanshiri; Shoaleh Bigdeli; Zahra Rahimi Moghadam; Meimanat Hosseini (Zanjan University of Medical Sciences and Health Services, 2018)
Background and Objective: One of the duties of education planners is following up dynamic programs with the goal of sustainable improvement and creation of optimal learning opportunity for learners. On the other hand, one of the most important challenges of clinical training is the tendency of teachers toward the use of traditional and difficult education and evaluation students to monitor their activities during the internship. This study aimed to combine two performance-based evaluation methods of logbook and DOPS (direct observing of the skill to perform clinical procedures) during the presentation and evaluation processes of field internship of BSc students of anesthesiology. Materials and Methods: This study was initiated since summer of 2011 in the country for the first time using just the posttest process for assessment. The stages of needs assessment, design, implementation and evaluation of internship were carried out using the combined method with the cooperation of 17 BSc students of anesthesiology in the paramedical school of Kashan University of Medical Sciences. Data analysis was performed in SPSS version 16 using descriptive statistics. Results: In this research, the level of impact of the combined method in various areas of learning, interaction with different treatment groups and total evaluation of education was reported to be 70.6, 76.5 and 100% (moderate to high), respectively. In addition, good and very good realization levels were recognized for general objectives of the course in all cases. Conclusion: According to the results of the study, application of the combined method led to the successful guiding of activities of students and their interaction with other groups during the course. In other words, use of this technique can be beneficial for improving team performance in education, increasing the acquisition of clinical skills and deeper understanding of concepts.